2019
DOI: 10.1111/jvh.13074
|View full text |Cite
|
Sign up to set email alerts
|

Age‐stratified anti‐HAV positivity in Pune, India after two decades: Has voluntary vaccination impacted overall exposure to HAV?

Abstract: Summary The degree of transmission of hepatitis A virus (HAV) is inversely proportional to the socioeconomic status of a community. Serosurveys conducted at Pune, India during 1982‐98 documented significant reduction in HAV exposure of paediatric, higher socioeconomic status (HSS) population. Anti‐HAV positivity (ELISA) in age‐stratified Pune population representing HSS and lower middle socioeconomic status (LMSS) (n = 1065) and infants till the age of 15 months (n = 690) was determined in 2017. Anti‐HAV posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…There were 14 seroprevalence studies from India [1124], 2 from Bangladesh [25, 26] and 1 from Pakistan [27], Sri Lanka [28] and Nepal [29] (Table 1, Table S1). The studies assessed seroprevalence of HAV antibodies (IgG and/or IgM) in healthy subjects and/or patients presenting with AVH symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 14 seroprevalence studies from India [1124], 2 from Bangladesh [25, 26] and 1 from Pakistan [27], Sri Lanka [28] and Nepal [29] (Table 1, Table S1). The studies assessed seroprevalence of HAV antibodies (IgG and/or IgM) in healthy subjects and/or patients presenting with AVH symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…HAV exposure was also significantly different across the various study populations [urban vs. rural: 31.8% vs. 55.3%, p = 0.005; high/middle socioeconomic status (SES) vs. low SES: 33.3% vs. 53.9%, p = 0.022; family size 3–5 vs. ≥ 6: 31.6% vs. 59.1%, p < 0.001] [19]. A study from Pune ( N = 1065 serum samples) found that in high SES subjects, there was a significant increase in anti-HAV positivity, while in the lower middle SES group, a significant decrease (6–25 years, p < 0.0001) was recorded compared with 1998 data [24]. Among healthy adult blood donors, HAV exposure was significantly lower for subjects with high vs. middle SES (89.0% vs. 95.9%, p < 0.01) [21].…”
Section: Resultsmentioning
confidence: 99%
“…previous HAV infection) has fallen over time. 26,[56][57][58][59] For example, Arankalle et al 56 reported that anti-HAV positivity decreased significantly from 1982 to 1998 among children from urban high socioeconomic populations (age 6-10 years: ~86% to 30.9%; age 11-15 years: ~94% to 46.9%; combined age p < .00001), but not in adults or urban lower middle socioeconomic populations. Das et al 57 reported that HAV-IgG seropositivity fell from 98.0% in 1982 60 to 54.1% in 1998 among those aged 15-24 years and from 98.6% 60 to 58.7% among those aged 25-34 years (both p < .05).…”
Section: Declining Hav Immunity In Indiamentioning
confidence: 99%
“…were much more likely to have had previous HAV infection) than high socioeconomic populations of the same age group, but by 2017, there was very little difference in seropositivity between the two populations. 59 Deoshatwar et al 61 have also reported results from the same region (for select age groups) for 2017 and These studies did not report study dates, so these dates are based on "received" and "accepted" publication dates. compared them with the same 1998 data as Arankalle et al 59 Figure 1B shows that the changes in seropositivity were less pronounced in the latter study.…”
Section: Declining Hav Immunity In Indiamentioning
confidence: 99%
See 1 more Smart Citation